IMPLEMENTASI KONSEP KAFĀ’AH BAGI PASANGAN MENIKAH PADA ERA MILENIAL - Aldira Oktarina; Zaiyad Zubaidi; Husni Mubarak (Prodi Magister Hukum Keluarga Pascasarjana UIN Ar-Raniry Banda Aceh, 2024)
As time goes by, in this era of the millennial generation, humans are required to be able to keep up with the changes that are occurring, where these changes can be in the form of changes in social order, economic conditions, lifestyle, technology, and so on. Problems that often occur in the domestic life of husband and wife are caused by an imbalance of Kafā’ah between the two partners, even in some cases of domestic violence can easily occur because there is no comparison and equality between husband and wife in establishing family life. together. And one of the problems in finding a good partner is the problem of Kafā’ah or what is usually called kufu' between the bride and groom. In this very significant era of the millennial generation, many of the marriage mechanisms that exist in Islamic sharia law have been formed in fiqh and are they still relevant at this time when the digital era is being formed in this millennial generation in Pidie. Each research is expected to provide certain benefits, both theoretically and practically. As for the benefits of this research, theoretically this research is an effort to provide knowledge and understanding so that it can contribute to thinking by the community and family law scholars about the concept of Kafā’ah in marriage. This research uses an empirical sociological approach, the type of research used is qualitative research, the data sources that will be used in this research are primary data sources and secondary data. The data collection techniques used in this research are interviews, observation, documentation and literature study. The data analysis technique used in this research is descriptive analysis data analysis technique. This research was conducted in Pidie Regency.The results of research conducted in Pidie Regency regarding the implementation of the Kafā’ah concept for married couples in the millennial era show that the millennial community in Pidie Regency accepts the concept of Kafā’ah as in fiqh, where every couple who wants to get married will see equality between prospective wife and future husband in terms of education, heredity, and also wealth.